La protección del patrimonio cultural en cinco elogiosas piezas jurisprudenciales de Argentina (Tema Central) - Damsky, Isaac Augusto (2014)
The aim is to discuss the main legal criteria developed in Argentina in regard to cultural and architectural heritage protection through the analysis of five court decisions and their main protection techniques. The goal is to raise awareness about the critical role of civil society in the protection and promotion of heritage and cultural values. The attempt is to highlight the importance of judge’s active role as a major figure in the field.